Shweta thakur Asked a Question
June 18, 2020 4:14 pmpts 30 pts
Expression for AH. We have AH = A (U + PV) = AU+ A (PV stituting the value of AU and P from eqns. (9) and (2), we get nRT an2 AH =-an| +A V-nb y2 V2 V-nb V V-nb = -an2 + nRT -an V, -nb +nb V -nb + nb +nRT V. V V, -nb = -2an V-nb nb nb =-2an +nRT 1+ 1+ V -nb V-nb 1 1 AH =-2an v, +n2 bRTI ..(11) V,-nb V-nb
  • 1 Answer(s)
  • 0 Likes
  • 3 Comments
  • Shares
  • Shweta thakur
    plz answer my last question
    Likes(0) Reply(0)
  • Lingareddy
    check it
    • cropped2853290378226128666.jpg
    Likes(0) Reply(2)
    Shweta thakur
    yes sir
  • Lingareddy Best Answer
    check it
    • cropped4871473992697700963.jpg
    Likes(0) Reply(1)
    Lingareddy
    r u understood